Study on damage mechanism of mudstone radiated by high energy laser - Lin, Gongshun; Huang, Peng; Feng , Xiaowei (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
As mining resources enter the deep stage, the rock strength is high, the use of traditional mechanical rock breaking technology, easy to cause serious wear of the drill bit, drill replacement costs increase, low rock breaking efficiency problems. Laser rock breaking technology uses the way of non-direct contact with rock mass to cause rock breaking, which greatly improves the speed of deep mining. In this paper, high energy laser experiments are carried out on mudstone . Scanning electron microscopy (SEM) is used to study the mudstone minerals before and after laser radiation, and the Brazilian splitting experiment is carried out on mudstone samples after laser test and he final experimental data and analysis results show that the mudstone mineral particles change from rough surface to smooth surface before and after laser radiation. The tensile strength of saturated mudstone samples is significantly improved after laser radiation.